Effectiveness of gastrodin for migraine: A meta-analysis - Xiu Zhou; Jingyi Shao; Xiuzhen Xie; Yingqi Xu; Tianyu Shao; Zhuqing Jin (Frontiers in Neurology, 2022)
BackgroundGastrodia elata Blume (GEB), a traditional Chinese medicine, has been widely used to treat dizziness, numbness of limbs, and infantile convulsion, among other issues. Gastrodin is the main component of GEB. This meta-analysis aimed to evaluate the efficacy and safety of gastrodin in the treatment of migraine.MethodsTen electronic databases, namely the Cochrane Library, Embase, EBSCO, PubMed, Web of Science, CENTRAL, CNKI (China National Knowledge Infrastructure), CBM (Chinese Biomedicine Database), WanFang, and VIP (Chinese Scientific Journals Database), were searched for randomized controlled trials (RCTs) of gastrodin for migraine published before September 2021. The data were analyzed by RevMan 5.3 software and evaluated by GRADEpro.ResultsA total of 1,332 subjects were included in 16 RCTs. The meta-analysis showed that gastrodin was significantly effective in treating migraine (RR = 1.21, 95%CI = [1.17, 1.27]), reducing the pain degree (MD = −1.65, 95% CI = [−2.28, −1.02]), reducing the frequency of migraine attack (SMD = −2.77, 95% CI = [−3.92, −1.62]), shortening the duration of migraine attack (SMD = −1.64, 95% CI = [−2.35, −0.93]), and slowing average arterial cerebral blood flow velocity (SMD = −3.19, 95% CI = [−5.21, −1.17]), as well as being safe.ConclusionsThis systematic review revealed gastrodin is effective and safe in the treatment of migraine.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=197094, identifier: CRD42020197094.